2015
DOI: 10.1364/oe.23.018256
|View full text |Cite
|
Sign up to set email alerts
|

High-power noise-like pulse generation using a 156-µm all-fiber laser system

Abstract: We demonstrated an all-fiber, high-power noise-like pulse laser system at the 1.56-µm wavelength. A low-power noise-like pulse train generated by a ring oscillator was amplified using a two-stage amplifier, where the performance of the second-stage amplifier determined the final output power level. The optical intensity in the second-stage amplifier was managed well to avoid not only the excessive spectral broadening induced by nonlinearities but also any damage to the device. On the other hand, the power conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In fact, the narrow peak reflects the typical temporal timescales of the internal noisy pulse packets; the broad baseline suggests that the pulse regime consists of packets with picosecond or subpicosecond range, possessing the fine inner temporal structure with randomly diverse noisy pulse. 119 At this stage, due to the low-level information collection through the traditional measuring scheme, including the averaged spectral measurement and the autocorrelation recording, it has been difficult to figure out the formation of the NLPs. In fact, the majority of chaotic pulses, including NLPs, found in the fiber lasers have not yet been resolved in real time.…”
Section: Rogue Waves Generated By Soliton Interactionmentioning
confidence: 99%
“…In fact, the narrow peak reflects the typical temporal timescales of the internal noisy pulse packets; the broad baseline suggests that the pulse regime consists of packets with picosecond or subpicosecond range, possessing the fine inner temporal structure with randomly diverse noisy pulse. 119 At this stage, due to the low-level information collection through the traditional measuring scheme, including the averaged spectral measurement and the autocorrelation recording, it has been difficult to figure out the formation of the NLPs. In fact, the majority of chaotic pulses, including NLPs, found in the fiber lasers have not yet been resolved in real time.…”
Section: Rogue Waves Generated By Soliton Interactionmentioning
confidence: 99%
“…Without any specific control, giant pulses are expected to pop up randomly and may not be reliable for applications. Yet, extensive studies about controllable giant pulses can be found in the literature [113][114][115][116] with the view of taking advantage of these sudden bursts for high precision remote-sensing [117] or photonic reservoir computing [118].…”
Section: Giant Pulses In Opticsmentioning
confidence: 99%
“…Despite chaotic distribution of radiation within noise-like pulses, the overall radiation power of noise-like pulses may be fairly stable [25,31]. Taking into account the possible high energy of noise-like pulses [48] and possible high average power of their radiation [49], such pulses may be considered as promising type of pumping radiation. The only requisite condition is absence of phase relations between the sub-pulses of the pumping radiation and the generated output radiation, and this condition is satisfied in a variety of applications.…”
Section: Noise-like Pulses As Pumping Radiation Sourcementioning
confidence: 99%